Quantification of damage and its effects on the compressive strength of an advanced ceramic. (1st March 2019) - Krimsky, Erez; Ramesh, K.T.; Bratcher, M.; Foster, M.; Hogan, James David
Highlights: CT can be used to determine 3-dimensional crack structures in ceramics. Internal cracks can lead to an increase in shear wave speed in ceramics. Frictional sliding may be more likely to occur in pre-damaged ceramics. Strain-rate strengthening effects may be diminished for cracked structures. Abstract: An understanding of the dynamic failure of damaged ceramics is important in protection applications, where the interaction of the projectile with cracked material is a contributing factor in the overall system performance. In this paper, we investigate the effects of pre-existing internal cracks on the quasi-static and dynamic compressive behavior of an advanced ceramic. We present experiments on a hot-pressed boron carbide in which internal cracks are generated through thermal shocking after which the initial material damage is quantified. Damage characterization was performed via Resonant Ultrasound Spectroscopy (RUS) and high-resolution Computed Tomography (CT). A computational procedure is developed to determine the three-dimensional structure of the internal crack network in the initially damaged material from a series of CT images. The failure and strength of the material is then evaluated experimentally. The uniaxial compressive strength of the predamaged boron carbide samples is determined under both quasistatic and dynamic loading scenarios and this is correlated with the pre-existing crack structure as determined by CT. Damaged samples were found to have average compressive strength of 1.14 GPa in quasistatic loading and 0.68 GPa in dynamic loading compared to 2.98 ± 0.6 GPa and 3.70 ± 0.3 GPa for pristine material, respectively. High speed photography employed during dynamic testing indicates that pre-existing cracks may lead to different failure mechanisms from what is normally seen in pristine material. Ultimately, these insights can be used to design improved materials that are more resistant to dynamic failure.